Minahasa Utara Menuju Bebas Stunting - Hendayana Hendayana (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
One of the development frameworks for North Minahasa to be more advanced is that the government continues to improve and improve programs on stunting prevention in North Minahasa Regency, because in the last 5 years the stunting prevalence rate in North Minahasa is quite high, even in 2018 North Minahasa Regency became a district. with the highest stunting rate in North Sulawesi reaching 35.44%. Therefore, the authors are interested in conducting research with the title " NORTH MINAHASA TOWARDS STUNTING FREE ". This study aims to find out how or what efforts are made by the North Minahasa Regency Government specifically at the Health Office regarding the stunting prevention and prevention process in order to realize stunting-free North Minahasa 2022, as well as what factors are the obstacles in this stunting prevention process. This study uses a qualitative descriptive research method with an inductive approach. Data collection techniques used are through interviews, observation and documentation. The data analysis technique used is data reduction, data presentation and then drawing conclusions. Based on the analysis conducted by the researchers, the stunting management process in North Minahasa Regency so far has been going well. All of this cannot be separated from the important role of the Regent of North Minahasa, Mr. Joune J.E Ganda, who always supports and provides input as well as programs in the handling of stunting in North Minahasa in order to realize a stunting-free North Minahasa in 2022.